1989
DOI: 10.1037/h0079774
|View full text |Cite
|
Sign up to set email alerts
|

Development, cross-validation, and assessment of reliability of the Christensen Dietary Distress Inventory.

Abstract: A series of two studies was conducted to develop and cross-validate a psychometric instrument capable of identifying individuals experiencing a dietary induced mood disturbance. The first study focused on the development of the Christensen Dietary Distress Inventory (CDDI) by identifying the items which would differentiate dietary responders from nonresponders. Dietary responders were identified as those individuals whose mood disturbance improved following a dietary intervention and deteriorated following eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 26 publications
(19 reference statements)
1
16
0
Order By: Relevance
“…Christensen, Krietsch, White, and Stagner (1985) demonstrated that a caffeine and refined sucrose free diet resulted in a reduction of emotional distress and reintroduction of these substances in a double-blind format resulted in a return of the distress. Several additional studies (Christensen, Krietsch, & White, 1989;Krietsch, Christensen, & White, 1988) have replicated these findings providing confirmation of the efficacy of this dietary intervention for ameliorating emotional distress. In a subsequent study Christensen and Burrows (1990) demonstrated that elimination of caffeine and refined sucrose from the diet was particularly effective in the amelioration of depression in a subsample of depressed individuals.…”
Section: Elimination Of Food As a Means O F Self-regulationsupporting
confidence: 54%
“…Christensen, Krietsch, White, and Stagner (1985) demonstrated that a caffeine and refined sucrose free diet resulted in a reduction of emotional distress and reintroduction of these substances in a double-blind format resulted in a return of the distress. Several additional studies (Christensen, Krietsch, & White, 1989;Krietsch, Christensen, & White, 1988) have replicated these findings providing confirmation of the efficacy of this dietary intervention for ameliorating emotional distress. In a subsequent study Christensen and Burrows (1990) demonstrated that elimination of caffeine and refined sucrose from the diet was particularly effective in the amelioration of depression in a subsample of depressed individuals.…”
Section: Elimination Of Food As a Means O F Self-regulationsupporting
confidence: 54%
“…(Beck, Ward, Mendelson, Mock, & Erbaugh, 1961) change scores for dietary responders and nonresponders separately and as a mixed group. (A reanarysis of data from Christensen, Krietsch, & White, 1989. ) This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Idiosyncratic Responsementioning
confidence: 98%
“…It would be erroneously concluded that an effect did not exist, when the null results existed only because the sensitive population was not sampled. Christensen et al (1989) have developed a psychometric instrument, the Christensen Dietary Distress Inventory (CDDI; Christensen, 1990), for the purpose of identifying distressed individuals responsive to caffeine and refined sucrose. The CDDI is a 34-item self-report inventory including statements responded to in terms of frequency of occurrence, reaction to, or perceived cause of a physical or psychological condition.…”
Section: Idiosyncratic Responsementioning
confidence: 99%
“…One argument is that affected individuals self-medicate, using food or drink to combat aversive mood states characterized by frustration, anxiety, or depression. Alternatively, some individuals may refrain from eating certain foods in order to avoid their putative behavioural toxicity, according to the view that certain dietary constituents are aetiological agents for various forms of dysfunctional behaviour and negative affect (Christensen et al 1989). For example, simple sugars have been variously blamed for disturbances in mood, sleep, and cognitive performance (Kruesi & Rapoport, 1986).…”
Section: Overviewmentioning
confidence: 99%